Aplikasi Kombinasi Vermikompos dan Pupuk Anorganik Terhadap Pertumbuhan Tanaman Melon (Cucumis melo L.) Varietas Glamour Yang Ditanam Secara Hidroganik - Abdul Haris; Mahayu Woro Lestari; Djuhari Djuhari; Nurhidayati Nurhidayati (AGRONISMA, 2021)
Hydroganically melon cultivation is a breakthrough from the impact of the continued reduction of agricultural land, a system that uses organic fertilizers as a supplier of nutrients needed by plants that can provide melon plants as expected. However, the content in organic fertilizers (vermicompost) is not sufficient to meet the growth of melon plants during fruit formation. Therefore, the hydroganic farming system is combined with inorganic fertilizers to complement the nutrients needed by plants. This study aims to determine the optimal dose of inorganic fertilizers needed by plants to provide the best growth, yield, and quality of melon plants. The experiment was conducted using a factorial randomized block design (RBD) with control using 2 factors. factor 1 is the vermicompost dose which consists of three levels: 300, 600, and 900 grams/pot, and factor 2 is the application of a combination of P and K fertilizers at a level (2.25 grams K + 2.25 grams P), (4.5 grams K + 2.25 grams P) and (2.25 grams K + 4.5 grams P) / plant. Parameters observed were Plant Length, Number of Leaves, Leaf Area, Fruit Weight, Fruit Diameter, Thickness of Flesh, Sugar Content. The results of this study indicate that there is an interaction in the combination of these treatments on the parameters of the weight of the cropping fruit and the thickness of the fruit flesh, the best yields are in the V3A1 treatment (vermicompost dose 900 g / pot with an application (2.25 gram K + 2.25 gram). P) / plant) with a value of 456.83 grams on the weight of the fruit planted. 913.67 in the weight of fruit per pot. and 3.20 on the average thickness of the pulp. And also V3A1 treatment Getting the best average sugar content with a value of 12.53Â° brix.